If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + (25 + -3) = 25 Combine like terms: 25 + -3 = 22 3x + (22) = 25 3x + 22 = 25 Reorder the terms: 22 + 3x = 25 Solving 22 + 3x = 25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + 3x = 25 + -22 Combine like terms: 22 + -22 = 0 0 + 3x = 25 + -22 3x = 25 + -22 Combine like terms: 25 + -22 = 3 3x = 3 Divide each side by '3'. x = 1 Simplifying x = 1
| -14.1=-4.7 | | x^2(a-b)-x(a+b)+2b=0 | | 318/63 | | sec(2x)=-(sqrt(2)) | | -11=61-60q | | 2x/6=50 | | 18-(4x-12)=0 | | 4cos^2x=5-(4sinx) | | -6f=72 | | -7y-2=-6y | | -11u+3u= | | 0=-1.3(4)+(-5.2) | | y=-1.3(4)+(-5.2) | | 9x^2+66x+121=0 | | 3x^2+4x=2x^2-2a-9 | | 8v=2v | | x^3-5x^2+3x+7=0 | | 361+256=x^2 | | 49f^2+14f+1=0 | | 617=x^2 | | w/7-5=2 | | 28+4y=16-2y | | y=in(3-2) | | F(x)=.41In(x+1)+31 | | 3x-4/2 | | .18=x(x+1.8) | | -10/-3= | | z=3(-10)/5(4) | | -32.1846273024+-1.92y^2+y^3=0 | | 0.8153726976+y^3-1.92y^2-33=0 | | t^2+23t+22=0 | | x^2+1x=2 |